The Mediating Effect of Self-efficacy on Nurses’ Emotional Intelligence and Social Responsibility - Hassanian, Zahra Marzieh; Fatahi, Azad; Amini, Roya; Ghaffari, Mohammad Ebrahim; Shadi, Danial (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Nurses need a wide range of skills and capabilities in their work. Among the most important are emotional intelligence, self-efficacy, and social responsibility. The present study examines the mediating effect of self-efficacy on nurses’ emotional intelligence and social responsibility. Methods: This descriptive and correlative study was carried out as a structural equation modeling work. The study population consisted of all nurses in the hospitals affiliated with Hamedan University of Medical Sciences in 2018. The participants were selected through ratio-stratified random sampling (n=223). Three standard Emotional Intelligence, General Self-efficacy, and Social Responsibility questionnaires were used for data gathering. Data analyses used SPSS v.24 and AMOS v.22 through structural equation modeling. Results: The results indicated that the direct effect of emotional intelligence on self-efficacy (p=0.001, r=0.56) was positive and significant. The indirect effect of emotional intelligence and social responsibility was also positive (p=0.148, r=0.130); however, it was insignificant. Still, there was no relationship between social responsibility and self-efficacy (r=0.001, p=0.971). The indices supported the model’s goodness of fit (GFI=0.948). The RMSEA value was equal to 0.73, which is in an acceptable range. Conclusions: Considering the study’s findings, improving nurses’ self-efficacy through education based on emotional intelligence is essential. In addition, emotional intelligence should be one of the criteria taken into account in the process of recruiting nurses.